Cutting and grabbing simulation of laparoscopic cholecystectomy in dekstop environment / Die Hui Hui - Die , Hui Hui (2005)
Virtual reality (VR) can be considered as the use of various computer graphics systems in combination with various displays and interface devices to provide the effect of immersion in an interactive three-dimensional computer-generated environment. The interaction between the user and the virtual environment is basically limited to the three sensory modalities of vision, tactile sensing and audio. VR has led to many researches for many years, to improve the technologies especially in medical surgical training simulation.The main objective of this research project is to develop a simple surgical training simulation on laparoscopic cholecystectomy by using the low end PC-based system. The software system was developed by “WorldToolKit” from Sense 8 Corporation in order to allow a surgeon to perform surgical training. This simulation concerns on the manipulation of the surgical tools to perform the basic techniques such as cutting and grabbing on the cystic duct at the gallbladder. Besides that, collision management also becomes a main concern in this project. In order to prove the validity of the system, it was tested on the collision detection and collision response between the virtual tools and the skin of the cystic duct. This response includes the visual and audio feedback and message prompt to acknowledge the user regarding the current status of the simulation. Method for grabbing and cutting also had been discussed in this project. Finally, this research also includes the testing on the effect of the complexity of the environment to the smoothes of the tool’s movement. Besides, the comparison between existing cutting method and new method had been analyzed. Conclusion is provided based on the result produced. Deficiencies and future enhancements of the system also had been discussed to improve the features of virtual surgical environment especially on the complexity of the fulcrum effect and force feedback on the simulation.